Análisis del material editorial para niños con discapacidad auditiva como apoyo al aprendizaje en la Unidad Educativa Especializada Dr. Camilo Gallegos D. - Gómez Gómez, Daniela Estefania (2024)
According to the Institute of Statistics and Census (INEC 2023), the rate of hearing impairment in Ecuador has decreased, since the disability in children between 6 to 12 years have 4.37% of the total percentage, since they have not focused on the realization of a good educational material. Therefore, the present research aims to analyze the editorial design and its relationship with learning for children in the canton of Ambato, through validation instruments that allow analyzing the corresponding variables for the development of the project. For this purpose, a mixed approach with deductive and inductive methodology was used to analyze the theories and concepts established to reach the solution, with the research modality in which the documentary and experimental bibliography was used, for data collection surveys, interviews and observation and analysis cards were used, which were applied to 3 graphic designers, 3 teachers, cards to children and surveys to 50 parents. As a result, editorial and educational parameters were obtained for the development of the proposal, which consists of establishing an editorial material that includes activities to support learning by merging educational material and sign language, containing a typography, images and colors suitable for children and thus they can interact in a better way with the material.